Military Audit In Handling Criminal Acts of Desertion by TNI Members Based on Article 87 of the Military Criminal Code at Military Audit II-08 Bandung - Mochamad Bintang Arvi Putra; Yusep Mulyana (International Journal Labs, 2025)
Desertion is one of the most serious offenses in the military environment, reflecting a lack of discipline and responsibility on the part of a soldier toward duties. This study aims to analyze the application of Article 87 of the Indonesian Military Criminal Code (KUHPM) to members of the Indonesian National Armed Forces (TNI) involved in desertion offenses within the jurisdiction of the Military Prosecutor's Office II-08 Bandung, to assess the effectiveness of the legal process, and to identify obstacles and legal solutions in law enforcement. This research employs a normative juridical method, using a literature study approach based on statutory regulations, legal doctrines, and relevant court decisions. The data are analyzed qualitatively to provide a comprehensive understanding of the application of military law in desertion cases. The results show that the implementation of Article 87 KUHPM by the Military Prosecutor's Office II-08 Bandung has been carried out firmly and in accordance with military legal procedures, from the investigation and prosecution stages to trial. The process has proven effective in enforcing discipline and deterring future violations, although some challenges remain, such as limited human resources, facilities, and difficulties in locating deserters. To enhance law enforcement effectiveness, efforts should focus on strengthening inter-agency coordination, improving legal personnel capacity, optimizing soldier rehabilitation, and increasing legal awareness within the TNI.